Denis Papin : sa vie, son œuvre - Vivier, Bernard (Comptes Rendus. Mécanique)
A doctor of medicine, Denis Papin never practised his art. He was very interested in science, and worked as an assistant to a number of great scientists, including Christian Huygens and Robert Boyle. An enthusiast of the experimental method, he invented the “Digesteur”, the ancestor of the “cocotte minute”, and laid down the experimental principles for the use of steam as a motive force. As a man of science who never traded his inventions, and who sought protectors capable of providing for the funding of his work, he was a nomadic scientist, even though his Protestantism kept him out of France. His life came to a difficult end, and he died in 1713 without seeing the industrial realisation of his work. In fact, in 1712, Thomas Newcomen and Thomas Savery produced the prototype of a steam pump to dry out mines, which was a great success and was nothing other than the implementation, on a large scale, of Papin’s experiments.